Evaluation of the Dependency and Intensity of the Virtual Water Trade in Korea†. (20th January 2016) - Lee, Sang‐Hyun; Yoo, Seung‐Hwan; Choi, Jin‐Yong; Shin, Ankook
Abstract: Trading in crops can be regarded as the primary source of water demand in terms of virtual water trade, and the main importers would have to consider the trading in crops from a water management perspective. The aim of this paper was to evaluate the dependency and intensity of the virtual water trade in Korea. The virtual water trade values of 41 crops were quantified from 2006 to 2010. About 9.5% of global blue water trade was captured by Korea through maize trade. In addition, we evaluated the water dependency and trade intensity of the virtual water trade. Water dependency was evaluated by examining the proportions of external to internal water footprints. Korea exhibited the highest water dependency of 99%, followed by maize and pulse crops. Virtual water trade intensity indicates the importance of trading partners. The results show that the USA and China have been the most important trading partners, and the trade intensity with Romania, Ukraine and Australia has increased from 2006 to 2010. These results, such as water dependency and trade intensity of virtual water trade, should be useful indices for sustainable crop trade and water management in Korea. Copyright © 2016 John Wiley & Sons, Ltd.